2013
DOI: 10.1038/ejcn.2013.81
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study to implement nutritional risk screening and evaluate clinical outcome and quality of life in patients with cancer

Abstract: BACKGROUND/OBJECTIVES: To implement nutritional risk screening and evaluate the relationship of nutritional risk to complication rate and quality of life in patients with cancer. SUBJECTS/METHODS: A total of 687 patients with cancer from two teaching hospitals in China were consecutively enrolled. Data were collected on the nutritional risk screening, application of nutritional support, complication and quality of life. RESULTS: The prevalence of nutritional risk at admission among the total, younger and elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Nonetheless, treatment-related side effects on nutritional status such as nausea and vomiting, appetite loss and diarrhea, which negatively affect patients' functional status and HRQoL (Dang et al, 2016) are commonly reported. While mounting evidence shows malnutrition is associated with decreasing HRQoL in cancer patients (Lis et al, 2012;Yu et al, 2013), the relationship between nutritional status and HRQoL is under-studied for breast cancer patients, who are at lower risk of under-nutrition as compared to other cancers (Lis et al, 2012). In spite of the negative impact of altered taste perception on calorie intake (Boltong et al, 2014;de Vries et al, 2017), weight gain was increasingly reported for breast cancer patients even during treatment (van den Berg et al, 2017), which may decrease their physical function and overall quality of life (QoL) (Fang et al, 2013), suggesting healthy eating habit for general health maintenance among the breast cancer patients is critical.…”
Section: Research Articlementioning
confidence: 99%
“…Nonetheless, treatment-related side effects on nutritional status such as nausea and vomiting, appetite loss and diarrhea, which negatively affect patients' functional status and HRQoL (Dang et al, 2016) are commonly reported. While mounting evidence shows malnutrition is associated with decreasing HRQoL in cancer patients (Lis et al, 2012;Yu et al, 2013), the relationship between nutritional status and HRQoL is under-studied for breast cancer patients, who are at lower risk of under-nutrition as compared to other cancers (Lis et al, 2012). In spite of the negative impact of altered taste perception on calorie intake (Boltong et al, 2014;de Vries et al, 2017), weight gain was increasingly reported for breast cancer patients even during treatment (van den Berg et al, 2017), which may decrease their physical function and overall quality of life (QoL) (Fang et al, 2013), suggesting healthy eating habit for general health maintenance among the breast cancer patients is critical.…”
Section: Research Articlementioning
confidence: 99%
“…The theories and methods behind nutritional support are constantly evolving. For patients who need nutritional support, choice of the appropriate method can enhance the recovery of patients and significantly improve clinical results and prognosis [13]. Due to a higher nutritional risk rate and functional degeneration, patients with multiple conditions are more common among elderly patients, who are more susceptible to disease and malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12,25,27 The frequent presence of malnutrition in cancer patients can limit their response to even the best therapies if nutritional issues are not appropriately managed. 30,32 Understanding baseline levels of nutritional status, physical function and quality of life is of growing importance in defining individualized supportive care plans for cancer patients. 12 In this INSCOC study, we have thus far collected more than 30,000 cases from 80 hospitals since 2013 and will recruit additional 20,000 cases in totally 100 hospitals in different regions in China in the next 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…9,[24][25][26][27][28] Recently the nutrition status of cancer patients has caught the attention of Chinese surgeons, physicians and dieticians. 22,[29][30][31][32][33][34][35] It is reported that the prevalence of malnutrition ranged from 12.6% to 54%, depending on the cancer type, cancer stage, and patient age. 22,30,32,33,35 The benefits of nutritional intervention have been shown in cancer patients with malnutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation